Isolation and Molecular Characterisation of Chlorogonium sp. from Industrial Wastewater - Abershi, Ajiduku Leyoa; Ikwebe, Joseph; Stephen, Ezeonu Chukwuma; Mafe, Alice Njolke; Abah, Moses Adondua (Darul Yasin Al Sys, 2024)
Microalgae are photosynthetic, unicellular microorganisms also known as phytoplankton. They are small plant-like entities. In this research, the sample were collected from cement factory in a sterilised 20L container wrapped with foil paper and were transported down to Federal University, Wukari where it was kept in refrigerator at biochemistry laboratory. Blue-Green media (BG-11) was prepared. Wastewater containing Microalgae obtained from cement wastewater pond were cultivated in BG-11 medium to determine the growth of the organism. BG-11 medium contained macronutrients, trace metals and some vitamins which aid the growth of the organism. The wastewater sample containing with suspected microalgae was inoculated (inoculum ratio = 25%) and incubated under atmospheric CO2 at room temperature (30±2°C) in our laboratory for two to three weeks during the incubation period. In order to purify the isolates, the upper growth layer was first decanted into a freshly produced medium and then plated on BG-11 media that had been solidified with 1% agar-agar. For several of the cultures, growth on the agar plates continued for around three weeks. Following repeated sub-culturing, the emerging greenish colonies were re-emerged into a sterile BG-11 agar medium. In isolation of organism from the industrial cement waste water, the isolate was identified by morphological and molecular identification by extracting the DNA, run the electrophoretic analysis and PCR using primers for 18S rRNA eukaryotic microalgal and then run the sequence analysis. The results of this study obtained, indicated that, the electrophoretic result show the band has 1800-2000base pair and the organism isolated from the industrial cement waste water were chlorogonium sp. with a percent similarity of 78.65% and accession number of OR886595 based on data Gene Bank blast results.